AB1223-HPR Beliefs and attitudes of italian nurses towards placebo and nocebo responses induced by contextual factors in clinical practice. (15th June 2017) - Testa, M; Rossettini, G; Geri, T; Viceconti, A; Colloca, L; Palese, A
Abstract : Background: Placebo and nocebo represent psycho-neuro-immuno-endocrinological responses commonly encountered in nursing care (1, 2). A new paradigm proposed the contextual factors (CF) as mediators and moderators of these responses (3). To date, the knowledge about the awareness of CF and their use in nursing is scant. Objectives: The goal of this study was to examine frequency of use, beliefs and attitudes of Italian specialised nurses regarding the contextual factors. Methods: In December 2016, through SurveyMonkey Software®, an online survey was conducted by sending a questionnaire to the members of four Italian Nursing Association, grouping nurses specialized in Neuroscience, Medical, Geriatric and Diabetic care. Behaviours, beliefs and attitudes of nurses about the implementation of CF in clinical practice were assessed by a 17 items questionnaire and resulting data were analysed by descriptive statistic. Results: Of the 1411 members of the involved Nursing Associations invited to participate to the survey 425 responded (30.1%). An high number of respondent nurses adopts CF often in their practice (42%). They believe that CF can positively influence acute pain (47.5%), chronic pain (61%) and rheumatologic disorders (42%). 34% of responders consider the use of CF, if it can determine beneficial psychological effects, as ethically accep table. 15.5% responders oppose to the adoption of CF when based on deception or if they undermines trust between nurses and patients. A relevant number of nurses (24%) do not communicate the use of CF to their patients and 19% implement CF as addition to other nursing interventions to optimize clinical responses. Nurses explain the power of CF through patient's expectation and psychological mechanism (11%). Conclusions: The Italian specialised nurses use CF quite frequently and believe that their use has the capacity of positively influencing the clinical outcome. Larger surveys are needed to understand the proportion of use of CF by nurses in common clinical practice in Italy. References: Miller LR, Miller FG. Understanding placebo effects: Implications for nursing practice. Nurs Outlook. 2015 Sep-Oct;63(5):601–6. Häuser W, Hansen E, Enck P. Nocebo phenomena in medicine: their relevance in everyday clinical practice. Dtsch Arztebl Int. 2012 Jun;109(26):459–65. Palese A, Rossettini G, Testa M. Placebo and nocebo responses in nursing practice: a discussion paper on the role of contextual factors. In revision at Nurs Inq. Disclosure of Interest: None declared